Chapter Handle with care/inclusivity Adaptation of cultural heritage - De Boeck, Muriel; Martens, Stefan Martens; Storgaard, Eva; Herssens, Jasmien; Vallet, Nathalie; Geldof, Dirk; Verreycke, Hélène; Annemans, Margo; Erkan, Yonca; Vaes, Kristof; De Vos, Els (Academia Press, 2023)
Industrial / commercial art & design